2012
DOI: 10.1210/jc.2011-3069
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid-Induced Changes in Circulating Monocyte Chemoattractant Protein-1 Levels May Contribute to Metabolic Dysfunction in Obese Men

Abstract: Initial alterations in sex steroid levels may contribute to metabolic dysfunction through adverse effects on adipokine levels in obese men. The direct adverse effects on MCP1, a chemokine highly linked to the development of metabolic dysfunction, were substantiated in a trial mimicking obesity-related alterations of sex steroid levels in healthy young males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…However, the latter reports were based on elderly men in whom the association between low testosterone and increased levels of inflammatory markers might be confounded by already manifest CVD and hence the direction of causality difficult to disentangle. A recent publication showed that transient elevation of estradiol levels with coincident lowering of testosterone affect several pro-inflammatory markers including MIP1a in young men [26]. The results are in agreement with our present findings regarding testosterone, but in contrast we did not find any link between estradiol and markers of LGSI.…”
Section: Discussionsupporting
confidence: 92%
“…However, the latter reports were based on elderly men in whom the association between low testosterone and increased levels of inflammatory markers might be confounded by already manifest CVD and hence the direction of causality difficult to disentangle. A recent publication showed that transient elevation of estradiol levels with coincident lowering of testosterone affect several pro-inflammatory markers including MIP1a in young men [26]. The results are in agreement with our present findings regarding testosterone, but in contrast we did not find any link between estradiol and markers of LGSI.…”
Section: Discussionsupporting
confidence: 92%
“…Several previous studies have also reported a similar negative correlation between serum IL-6 and testosterone [16, 23, 29, 30], with the majority of these investigators suggesting that the observed increase in IL-6/inflammation with obesity was due to a withdrawal of testosterone’s immunosuppressive effect [1315, 29, 30]. However, we believe that IL-6 may be directly inhibiting testicular function, thereby leading to a reduction in testosterone and AMH levels.…”
Section: Discussionsupporting
confidence: 64%
“…Secondly, while we have reported very significant positive correlations between LBP and IL-6, and negative correlations between IL-6 and testosterone levels, the purely observational nature of our study does not enable us to draw definitive cause-effect relationships. However, given previous reports linking IL-6 exposure to impaired testosterone production [16, 23, 29, 30], we do believe that metabolic endotoxaemia related increase in IL-6 production is likely to play some role in impairing testicular function in obese men. We also acknowledge that LBP is only an indirect measure of endotoxaemia and the passage of gut bacteria derived endotoxin into the circulation.…”
Section: Discussionmentioning
confidence: 66%
“…35,36 In general, hormones, interleukins and chemokines may trigger a response even if their circulating amount is low. 37,38 Hypoxia induced by treatment with 1% O 2 has been shown to elevate VEGFA mRNA stability; 27 however, in our current model, the halflife of the VEGFA mRNA was not affected by the chemical inducer CoCl 2 , while transcription was moderately increased (Fig. 2), perhaps through a CoCl 2 -elicited increase in HIF1a expression levels.…”
Section: Discussionmentioning
confidence: 53%